Combating Terrorism - Davis, Lois M.; Mariano, Louis T.; Pace, Jennifer E.; Cotton, Sarah K.; Steinberg, Paul (RAND Corporation, 2023)
Organizations varied in how they financed these efforts-some increased internal spending or reallocated resources-and in receipt of external funding. ¥